'Publication', papyri, and literary texts: process and presentation - Kondakova, D (2022)
What do we mean when we say that an ancient author 'published a treatise' or that Vergil's Aeneid was 'left unpublished'? Are we even allowed to make such statements, in the absence of publishing houses? Oral practices held an important place in the literary world, and Greek and Latin books were copied by hand. Was their literary culture, then, completely different from ours? This thesis aims to answer such questions by approaching 'publication' from the perspective of the authors and readers involved, and by comparing the evidence across extant literary texts with insights from papyri.